Theoretical prediction of superconductivity in monolayer CoO2. Issue 36 (11th September 2019) - Nguyen, Duc-Long; Hsing, Cheng-Rong; Wei, Ching-Ming
Abstract : Implication of the coexistence of intrinsic ferromagnetism and superconductivity in monolayer CoO2 . Abstract : Motivated by the synthesis of the layered structure CoO2 via Li atom deintercalation from Li x CoO2, herein, we investigated the electronic structure, lattice dynamics, electron–phonon interaction, and superconductivity of monolayer CoO2 using first-principles calculations. This 2D material was predicted to have a ferromagnetic ground state with a metallic band structure and the total magnetization of 0.83 μ B . Remarkably, the non-spin polarized calculations show that the monolayer CoO2 possesses phonon-mediated superconductivity at 25–28 K owing to its intermediate to strong electron–phonon coupling (EPC). The rather strong EPC in this compound is mainly driven by the acoustic phonons, making this compound one of the highest-temperature superconductors among the existing 2D materials. Moreover, the CoO2 sheets could be synthesized via exfoliation from bulk CoO2 owing to the relatively small interlayer binding energy while maintaining its stability under normal experimental conditions. Compared to its bulk and bilayer counterparts, monolayer CoO2 was found to have highest EPC.